A systematic review of epidemiology and outcomes of Crohn's disease-related enterocutaneous fistulas. Issue 45 (11th November 2022) - Iglay, Kristy; Bennett, Dimitri; Kappelman, Michael D.; Reynolds, Kamika; Aldridge, Molly; Karki, Chitra; Cook, Suzanne F.
Abstract : Background: Enterocutaneous fistulas (ECF) are rare sequelae of Crohn's disease (CD) that occur either postoperatively or spontaneously. ECFs are associated with high morbidity and mortality. This systematic literature review assesses the disease burden of CD-related ECF and identifies knowledge gaps around incidence/prevalence, treatment patterns, clinical outcomes, healthcare resource utilization (HCRU), and patient-reported outcomes (PROs). Methods: English language articles published in PubMed and Embase in the past 10 years that provided data and insight into the disease burden of CD-related ECF (PROSPERO Registration number: CRD42020177732) were identified. Prespecified search and eligibility criteria guided the identification of studies by two reviewers who also assessed risk of bias. Results: In total, 582 records were identified; 316 full-text articles were assessed. Of those, eight studies met a priori eligibility criteria and underwent synthesis for this review. Limited epidemiologic data estimated a prevalence of 3265 persons with ECF in the USA in 2017. Clinical response to interventions varied, with closure of ECF achieved in 10% to 62.5% of patients and recurrence reported in 0% to 50% of patients. Very little information on HCRU is available, and no studies of PROs in this specific population were identified. Conclusion: The frequency, natural history, and outcomes of ECF are poorly described in the literature. The limited number of studies included in this review suggest a high treatment burden and risk of substantial complications. More robust, population-based research is needed to better understand the epidemiology, natural history, and overall disease burden of this rare and debilitating complication of CD.